"Trust Me, I am the One Who Will Drain the Swamp": an Interview With Walden Bello on Fascism in the Global South - Schaffar, Wolfram (2018)
Abstract: Since the election of Narendra Modi in India in 2014 and Donald Trump in the USA in 2016, political analysts and commentators around the globe have increasingly used the concept of fascism to capture the rise of new right-wing authoritarianism in various countries. Activists and academics in Europe are much more reluctant to use the word fascism, for several reasons. One reason is that - because of the alarming associations which fascism evokes in German - the term was often instrumentalized, and used to discredit political opponents, without a sound theoretical analysis. There is also a big reluctance to transfer the term to countries outside Europe, especially to the countries in the South - because it would further relativize the concept. Walden Bello is a prominent voice who started using the concept of fascism since early 2017 for the new regime under Rodrigo Duterte in the Philippines. He repeated his analysis of Duterte as a “fascist original” and his regime as "creeping fas